The Role of School Psychologists in Supporting Adolescents With ADHD. (December 2020) - Wiener, Judith
This paper integrates the findings from the four studies in this special issue and discusses the implications for school psychology practice. Our research indicates that adolescents with attention-deficit hyperactivity disorder (ADHD) are typically aware of their difficulties and believe that their problem behaviors are pervasive, uncontrollable, and stigmatizing. They are especially concerned about their social relationship problems. In this paper, I argue that school psychologists play an important role in addressing these concerns by conducting assessments in which the adolescent is a partner in the process and by providing evidence-based mental health interventions in the school setting.